The Effect of Marketing Activities on Profitability with Others Comprehensive Income as Moderation: Evidence from Southeast Asia - Andriana, Ririn; Kusuma, Marhaendra; Mohd Kasim, Che Manisah; Barreto, Carlos Afonso (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
This research aims to know moderated of others comprehensive income in link of marketing activities on the profitability of financial sector firm in the Southeast Asia region. Research on profitability determination has been widely conducted, but testing the moderating role of Others Comprehensive Income (OCI) in link marketing activities on financial profitability in financial sector companies has not been widely conducted. This is important because financial sector companies have large financial assets. The source of funding comes from funding funds that are inseparable from marketing activities. Ownership of large financial assets has an impact of other comprehensive income (OCI), especially the type of unrealized earnings from adjustment assets include financial types that are ready to be realized (AFS). Observation data of 612 from the financial statements of a sample of 153 financial sector companies in 2020 - 2023 in five Southeast Asian countries, namely Indonesia, Thailand, Malaysia, Singapore, and the Philippines. Data analysis using Moderated Regression Analysis and showing the results that the existence of OCI in financial sector companies is proven to strengthen the positive impact activities of marketing to ROA or profitability. The originality of this study is to test OCI’s moderated in link marketing activities on profitability. Large OCI AFS ownership in financial sector companies is important information for investors regarding future profitability, because AFS will be realized in the future, and its realization will certainly affect net income.